Utilization of Waste Fabric into Economic Value Products in Sawah Lebar Village, Bengkulu - Reflis, Reflis; Utama, Satria Putra; Hayati, Nur (Altifani Journal: International Journal of Community Engagement, 2021)
Patchwork waste is an inorganic waste that is difficult to be decomposed by the environment. Patchwork waste is often a problem because many convection industries only allow patchwork waste to accumulate and then be burned and become environmental pollution because it creates smoke and gases that are not good for health. Therefore, it is necessary to reuse the patchwork waste into products that have selling power and aesthetic value. The implementation method in this service activity starts from field visits/initial observations regarding partner conditions and problems, offering solutions and program socialization, program implementation which begins with lectures on the importance of utilizing patchwork waste and demonstrations and the practice of making these products. This service activity aims to change the awareness and concern of the people of Sawah Lebar Village towards the existence of inorganic waste around the environment, especially patchwork and to equip mothers to be creative in processing patchwork waste into goods that have selling power so that they can help the family economy. The service activities that have been carried out provide education to the community around the Sawah Lebar Village, Bengkulu City, especially RT 02 about the importance of processing patchwork waste so that it becomes a product of economic value. This service activity is carried out in two stages, namely: 1. Counseling on the importance of processing patchwork waste, 2. The tutorial on processing the patchwork waste into a more useful product, namely the mask connector.